Effect of Nickel Pre-Plated on Microstructure and Oxidation Behavior of Aluminized AISI 316 Stainless Steel. Issue 1 (2nd January 2016) - Karimzadeh, A.; Rouhaghdam, A. Sabour
Abstract : Aluminizing of nickel pre-plated AISI 316 is prepared by a high-activity pack at 1050 °C. The effect of initial nickel layer with different thicknesses on microstructure and oxidation behavior of coating is investigated. After aluminization, the surface microstructure of stainless steel mainly consists of β-(Fe, Ni)Al as matrix with β-FeAl + α -(Fe, Cr) precipitates and an inter-diffusion layer with γ phase. Aluminized coating on specimens with 10 and 20 µm primary thicknesses of the nickel layer includes three layers. The outer zone is made up of β-NiAl thin layer and a β-(Fe, Ni)Al layer. As the nickel layer increases to 50 and 100 µm, aluminide layers consist of outer and inner zone with β-NiAl and Ni3 Al phase, respectively. Oxidation tests at 950 °C show that the oxidation resistance of aluminide coatings improves and oxidation kinetics follows a sub-parabolic rate law by increase in thickness of initial nickel layer.